Bis-chelate iron(II) complex with a 1, 5-diaza-3, 7-diphosphacyclooctane ligand: X-ray structure and redox properties. (27th May 2019) - Khrizanforova, Vera V.; Fayzullin, Robert R.; Karasik, Andrey A.; Budnikova, Yulia H.
Abstract: The bis-chelate dichloride iron(II) complex ( 1 ) with a 1, 5-diaza-3, 7-diphosphacyclooctane ligand (P Ph 2 N Bn 2 ) was synthesized and characterized by single crystal X-ray diffraction (XRD). Redox properties of the iron (II) complex was studied by cyclic voltammetry (CV). Graphical Abstract: UF0001